La Ley Orgánica de Extinción de Dominio y el principio de irretroactividad - Pilco Cujilema, Yesenia Elizabeth (2023)
In the present investigation, an analysis of the Organic Law of Domino Forfeiture is carried out with the objective of determining, through a legal, doctrinal and critical analysis, if it violates the principle of non-retroactivity of the law and affects the right to legal certainty. To achieve this objective, the legal nature of asset forfeiture, its legal configuration in comparative law and in international instruments related to corruption, were studied to verify the results of this analysis with the principle of non-retroactivity of the law and its relationship. with legal certainty. Qualitative research was carried out based on the inductive, analytical and descriptive methods applied to the analysis of books, scientific articles, codes and materials available on the web on domain extinction and the principle of nonretroactivity of the law and the right to legal security. It should be noted that the project for the Organic Law on Forfeiture of Domino objected by the President of the Republic did affect the principle of non-retroactivity and legal certainty, but through its opinion the Constitutional Court declared these regulations unconstitutional, therefore it is concluded that the current Domino Forfeiture Organic Law is in accordance with the requirements of the principle of nonretroactivity and respects the right to legal certainty.